Desenvolvimento local : uma amostragem do município de Passo Fundo no período de 2005 a 2011 - Cittolin, Marcos Alexandre (2013)
This study had for a proposition to analyze impactful elements in Passo Fundo, addressing theories inherent to regional, local and sustainable developing. Analyzing the relation of each theory with the new concept of economic development, having as basis the development indicators, specifically the ones covering infrastructure and economic development. We comprehend that the theoretical contribution on development and the multiple dimensions related to this planning must take into account the social and economic dimensions. Thus, through a theoretical and technical evaluation on local development, taking as spatial area Passo Fundo s region and the period between 2005-2011. Relating actions of local power, other powers and private initiative to the municipal development based on indicators, in a manner that we discuss about the major bases of information and sketch a qualitative analysis of its key economic characteristics. We comprehend that the indicators appear as a tool for monitoring and evaluating goals and targets to be reached, as well as serving as measures and escorts to the implementation of public policies, indicators can also make objectives more specific. Currently giving emphasis on the creation of indicators whose implementation may be possible at a local and regional level and not just global